PSIKOEDUKASI “STARTING WITH YOURSELF” SEBAGAI UPAYA PENINGKATAN KEPEMIMPINAN DIRI DAN KINERJA OPTIMAL - A'yun, Qurrota; Raja Oloan Tumanggor; P. Tommy Y. S. Suyasa (Badan Pelaksana Kuliah Kerja Nyata Universitas Lampung, 2025)
This Community Service Program aimed to enhance the understanding and skills of employees at PT MTI in applying self-leadership as an effort to achieve optimal performance within a dynamic work environment. The program was implemented through a psychoeducational webinar entitled “Starting with Yourself,” which was attended by 110 employees from various divisions and job levels, demonstrating a high level of participation. The psychoeducational content covered fundamental leadership concepts, behavior-focused strategies, natural reward strategies, and constructive thought strategies. Evaluation was conducted using pre-test and post-test assessments to measure improvements in participants’ understanding. The results indicated a significant increase in employees’ knowledge after joining the webinar, as reflected in their enhanced ability to comprehend, integrate, and apply self-leadership concepts compared to their initial understanding prior to the program. Active engagement in ice-breaking activities, discussions, and question-and-answer sessions further contributed to the effectiveness of the learning process. These findings suggest that psychoeducation is an effective method for strengthening employees’ self-regulation capacities and readiness to meet the demands of work in the telecommunication industry. This program is expected to serve as a foundation for the development of subsequent leadership-based training initiatives aimed at continuously improving the quality of human resources.